Translating Dialect in Fiction: A Case Study - Semėnaitė, Viktorija; Maskaliūnienė, Nijolė (Vertimo studijos, 2017)
[full article and abstract in Lithuanian; abstract in English] The article focuses on the translation of dialect in fiction. Many authors regard it as one of the most complicated issues in translation because the translator has to make a choice between translating it as a language in its own right or make an attempt to make the translation sound “dialectal”. In many cases dialect serves specific functions of characterising protagonists, creating a special atmosphere or setting in the Source Text. The translator’s role is to transfer these functions into the Target Text for a reader of the translation. This article aims to identify the ways in which dialogue is translated from English into Lithuanian in the example of Burnett’s book for children, The Secret Garden, with a special focus on its functions in the Source Text. This book was chosen because critics almost unanimously claim that the Yorkshire dialect employed in it serves as a protagonist itself, therefore its role is very important for the development of the narrative, and, as such, cannot be ignored in translation. The study is based on the analysis of dialectal markers (phonetical, lexical, syntactic and morphological), and the ways they are rendered in the text. Reference is made to the ten strategies of dialect translation proposed by Leszek Berezowski (1997), including neutralization, lexicalization, partial translation, transliteration, pidginization and others. The results of this analysis show that the translator used fewer dialectal markers than there were in the original, and the most common translation strategy was neutralisation. Yet, those instances that were selected as important for the development of the narrative were rendered using strategies of lexicalization and colloquialization. This way the translator managed to preserve the coherence of the text, and the functions and stylistics of the work.